Produtos naturais fermentados : ativação de mecanismo de defesa e controle de cercosporiose em milho pipoca - Suárez, David Fernando Posso (2017)
Resistance induction (IR) in plants by natural products has been the object of several studies, being activated by elicitor molecules of biotic or abiotic origin. Elicitors activate resistance mechanisms such as Pathogen-Related Proteins (PRPs) and phytoalexins, which act to protect plants from the development of the pathogen. The present work aimed to verify the activation of PRP (peroxidase, catalase, polyphenoloxidase and ?-glucanases) in popcorn plants and phytoalexin in soybean and bean plants treated with different concentrations of the commercial product Microgeo®and a Biofomulate made with lemon grass fermented. Analyzing the PRP's enzymes, it was observed that Microgeo®activated the increase of an enzymatic activity and that this induction is more pertinent to the period of application than the dosage used.Microgeo®is also capable of inducing the accumulation of glyceolinin soybean plants. On the other hand, it was observed that the Bioformulate also activates and increases the activity of these enzymes, and that this accumulation is related to the period of application, but not to the dosage used, however the Bioformulate does not induce accumulation of glyceolin in soybean plants. The application of Microgeo®não presents a efficiency significantin controlling the Cercosporiose in popcorn plants